Analysis of Ant Communities Comparing Two Methods for Sampling Ants in an Urban Park in the City of São Paulo, Brazil - Ribeiro, Felipe M. [UNESP]; Sibinel, Neiva; Ciocheti, Giordano; Campos, Ana E. C. (Univ Estadual Feira Santana, 2012)
This study aimed to analyze the species composition and functional groups of the ant community and to assess the efficiency of two sampling methods, pitfall and leaf litter sampling, in an urban park. A total of 1,401 ants were collected, which belonged to six subfamilies and 36 species. The predominant species was Wasmannia auropunctata (present in 45.36% of the samples), while the functional group of opportunistic ants were the most frequent (present in 83.75% of the samples) and abundant (95.29% of the total collected specimens) functional group. The Jaccard Similarity Index showed a low similarity between the two sampling methods, as the difference of the number of individuals for each species between these two methods was not significant in only one case (Linepithema sp. 1, p = 0.4561). The fungus-growing and cryptic ants were more collected in leaflitter samples (p<0.0001; p = 0.0348 respectively). Although there was no significant difference (p = 0.6397) between the two sampling methods for the total individuals of opportunistic ants, more species of this group were collected in pitfall traps. This difference was not significant because of the high presence of W. auropunctata, an opportunistic ant, in samples of leaf litter. Due to the predominance of tramp ants in the studied area, this article illustrates the importance of green urban areas in ant control strategies, since these sites could be used as a source of new colonization for these ants. Furthermore, the combination of the two sampling methods seems to be complementary for obtaining a more complete picture of the ant community.
Keywords: ant community; urban areas; tramp ants; functional group; urban areas; pitfall trap; leaf litter sample